2001
DOI: 10.1007/s003300000557
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic dysfunction in patients with rheumatoid arthritis of the cervical spine. Predictive value of clinical, radiographic and MR imaging parameters

Abstract: The aim of this study was to evaluate if subjective symptoms, radiographic and especially MR parameters of cervical spine involvement, can predict neurologic dysfunction in patients with severe rheumatoid arthritis (RA). Sequential radiographs, MR imaging, and neurologic examination were performed yearly in 46 consecutive RA patients with symptoms indicative of cervical spine involvement. Radiographic parameters were erosions of the dens or intervertebral joints, disc-space narrowing, horizontal and vertical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 0 publications
0
20
0
4
Order By: Relevance
“…Thirteen studies described the assessment of cervical spine involvement in RA, summarised in table 4 108 – 120. No studies explored the appropriate frequency for monitoring change in the cervical spine; Yurube et al 118 investigated baseline features on CR predictive of future cervical instability and found that patients with baseline deforming hand changes, cervical vertical subluxation (VS), and subaxial subluxation showed more progression in VS and subaxial subluxation at 5 years, and Reijnierse et al 120 identified that baseline MRI atlas erosions and reduced subarachnoid space were associated with clinical neurological dysfunction at 1 year.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies described the assessment of cervical spine involvement in RA, summarised in table 4 108 – 120. No studies explored the appropriate frequency for monitoring change in the cervical spine; Yurube et al 118 investigated baseline features on CR predictive of future cervical instability and found that patients with baseline deforming hand changes, cervical vertical subluxation (VS), and subaxial subluxation showed more progression in VS and subaxial subluxation at 5 years, and Reijnierse et al 120 identified that baseline MRI atlas erosions and reduced subarachnoid space were associated with clinical neurological dysfunction at 1 year.…”
Section: Resultsmentioning
confidence: 99%
“…Rheumatoid arthritis, for example, usually involves the cranio-cervical junction, even though recent studies report that the appearance of neurological signs in patients with rheumatoid arthritis may be secondary to alterations at a lower level, such as encroachment of the subaracnoid space between C1 and C7 [52].…”
Section: Differential Diagnosismentioning
confidence: 97%
“…Numerous experimental studies using plain radiography, computed tomography, and MRI have reported the pathogenesis and biomechanics of the upper cervical spine in patients with rheumatoid arthritis (RA) or trauma. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] However, to the best of our knowledge, there are few reports on the kinematic relationships of the occipitoatlantoaxial complex in non-RA or nontraumatic patients using dynamic MR images, and many points on these kinematics relationships remain to be clarified. The objective of this study is to elucidate the kinematic relationships of the upper cervical spine in patients with general age-related cervical spondylosis with Kinetic MRI (K-MRI).…”
mentioning
confidence: 99%